Anophthalmia and microphthalmia - Verma, Amit S (BioMed Central, 2007)
Anophthalmia and microphthalmia describe, respectively, the absence of an eye and the presence of a small eye within the orbit. The combined birth prevalence of these conditions is up to 30 per 100,000 population, with microphthalmia reported in up to 11% of blind children. High-resolution cranial imaging, post-mortem examination and genetic studies suggest that these conditions represent a phenotypic continuum. Both anophthalmia and microphthalmia may occur in isolation or as part of a syndrome, as in one-third of cases. Anophthalmia/microphthalmia have complex aetiology with chromosomal, monogenic and environmental causes identified. Chromosomal duplications, deletions and translocations are implicated. Of monogenic causes only SOX2 has been identified as a major causative gene. Other linked genes include PAX6, OTX2, CHX10 and RAX. SOX2 and PAX6 mutations may act through causing lens induction failure. FOXE3 mutations, associated with lens agenesis, have been observed in a few microphthalmic patients. OTX2, CHX10 and RAX have retinal expression and may result in anophthalmia/microphthalmia through failure of retinal differentiation. Environmental factors also play a contributory role. The strongest evidence appears to be with gestational-acquired infections, but may also include maternal vitamin A deficiency, exposure to X-rays, solvent misuse and thalidomide exposure. Diagnosis can be made pre- and post-natally using a combination of clinical features, imaging (ultrasonography and CT/MR scanning) and genetic analysis. Genetic counselling can be challenging due to the extensive range of genes responsible and wide variation in phenotypic expression. Appropriate counselling is indicated if the mode of inheritance can be identified. Differential diagnoses include cryptophthalmos, cyclopia and synophthalmia, and congenital cystic eye. Patients are often managed within multi-disciplinary teams consisting of ophthalmologists, paediatricians and/or clinical geneticists, especially for syndromic cases. Treatment is directed towards maximising existing vision and improving cosmesis through simultaneous stimulation of both soft tissue and bony orbital growth. Mild to moderate microphthalmia is managed conservatively with conformers. Severe microphthalmia and anophthalmia rely upon additional remodelling strategies of endo-orbital volume replacement (with implants, expanders and dermis-fat grafts) and soft tissue reconstruction. The potential for visual development in microphthalmic patients is dependent upon retinal development and other ocular characteristics.